Capsulorhexis: Pearls and pitfalls - Mohammadpour, Mehrdad (Elsevier, 2011)
A critical step in phacoemulsification (as well as extracapsular cataract extraction) is making a window in anterior capsule wall (i.e. anterior capsulotomy). Continuous Curvilinear Capsulorhexis (CCC) has become recognized as the standard method of anterior capsulectomy. Techniques employed for CCC have undergone sustained evolution. The present review evaluates elementary principles of CCC. Management of CCC in the presence of small pupil and pseudoexfoliation syndrome is discussed. Main differences of pediatric CCC from its adult-style counterpart and finally several techniques of rescue of an extending capsulorhexis are also reviewed.